Targeting TRPC-5 Channel Inhibition to Improve Penile Vascular Function in Erectile Dysfunction - El Assar, Mariam; García-Gómez, Borja; La Fuente, José M; Alonso-Isa, Manuel; Martínez-Salamanca, Juan I; Fernández, Argentina; Sosa, Patricia; Romero-Otero, Javier; Rodríguez-Mañas, Leocadio; Angulo, Javier (International journal of molecular sciences, 2025)
Canonical transient receptor potential (TRPC) channels contribute to calcium homeostasis, which is involved in penile vascular contractility and erectile dysfunction (ED) pathophysiology. We evaluated the impact of TRPC5 inhibition on endothelial function in penile vascular tissue from aging rats and ED patients and its effect on the relaxant efficacy of PDE5 inhibitors. TRPC inhibitor-induced endothelial and neurogenic relaxations were evaluated in corpus cavernosum (RCC) from a rat model of aging-related ED and in human penile resistance arteries (HPRAs) and corpus cavernosum (HCC) from ED patients and organ donors (NoED). The TRPC5 inhibitor, AC1903, was more effective than TRPC3 and TRPC4 inhibitors in relaxing aged RCC and HCC and HPRA from ED patients. In addition to enhancing endothelial and neurogenic relaxations in RCC from aged animals, AC1903 improved endothelium-dependent relaxation in both HCC and HPRA from ED patients but not in tissues from NoED. Cavernosal expression of TRPC5 was not different between ED and NoED subjects. AC1903 potentiated relaxations to the PDE5 inhibitor, tadalafil, in HCC/HPRA from ED patients. TRPC5 inhibition improved penile vascular function in aged rats and patients with ED. TRPC5 inhibition could be a potential therapeutic target for ED, particularly when combined with PDE5 inhibitors to enhance treatment outcomes.